Assessing the welfare impact of the 2001 tax reform on dual-earner families - Julie L. Hotchkiss; Robert E. Moore (Federal Reserve Bank of Atlanta, 2007)
We assess the 2001 income tax reform to determine its welfare impact across families with different characteristics. A household labor supply model is estimated to account for variable behavioral responses by family type. We find that while higher-education families received a larger share of the welfare gain generated from lower marginal tax rates, it was the lower-education families that provided the bulk of the additional labor supply motivated by the tax reform. We also find differing welfare gains across families with different numbers of children, highlighting the importance of allowing responses to vary across family characteristics when assessing the welfare impact of a policy change.
Keywords: J22; H31; H23; I31; 330; family labor supply; tax reform; family welfare; family utility